Pengaruh Penggunaan Fitur Simulasi Pada Codin Berbasis Web Terhadap Hasil Belajar Elemen Algoritma Dan Pemrograman Siswa Kelas X SMK - Moch. Anang Ardiansyah; Elvira Wardah (CV. SINAR HOWUHOWU, 2026)
The abstract and prosedural character of Algorithm and Programming material often makes it difficult for students to grasp without an interactive medium to support comprehension. At SMKS YPM 4 Taman, classroom instruction had relied mainly on printed modules and verbal explanation, leaving many students with only a partial grasp of the subject. This study set out to examine how the simulation feature embedded in Codin, a web-based learning medium, influences students' cognitive learning outcomes on the Algorithm and Programming element. Forty-five Grade X RPL students at SMKS YPM 4 Taman took part as research subjects, with data gathered through a pre-experimental, one-group pretest-posttest design. The collected data were processed using the Shapiro-Wilk normality test, a Paired Samples T-Test, and an N-Gain calculation. Both pretest and posttest scores were found to be normally distributed, with p-values of 0.063 and 0.408. The Paired Samples T-Test produced a p-value of 0.001, below the 0.05 threshold, pointing to a meaningful rise in cognitive learning outcomes once Codin was introduced. This rise was echoed in the N-Gain result, which averaged 0.689 and fell within the moderate category.